Are the acute phase proteins related to anestrus in primiparous water buffaloes? Preliminary results - Frank Díaz-Huerta; Anthony Meléndez-Becerra; Justin Dijak; Héctor Nava-Trujillo (Revista Científica)
Primiparous water buffaloes are a group with more risk for low reproductive performance, mainly due to a long period of postpartum anestrus, which could have a multifactorial or- igin. It is unknown if inflammatory diseases may promote the long anestrus period in primiparous buffaloes. Therefore, this preliminary analysis aimed to compare C reactive protein and fibrinogen levels, two acute phase proteins, and body condi- tion score and cholesterol levels in primiparous water buffaloes during the early postpartum and after a long anestrus period. To this, ten primiparous water buffaloes from a commercial farm in La Fria, Tachira, Venezuela, were submitted to a reproductive ultrasonographic evaluation; no signs of uterine disease or cor- pora lutea were observed in any buffalo; and therefore, these were considered in anestrus and grouped as early postpartum (n=4, mean of postpartum days 15±2.70) or prolonged anestrus (n=6, mean of postpartum days 124.5±36.55, p< 0.05). More- over, the body condition score was evaluated using a 1 to 5 scale with 0.25 increments (1 = thin, 5 = fat), and blood sam- ples were collected to measure the levels of C-reactive protein (by ELISA), fibrinogen (by Clauss assay), and cholesterol (by Colorimetric method). All the means were compared by T-test using R studio; additionally, a correlation analysis was carried out. No differences were observed for any of the studied vari- ables. Body condition score was lower than 3 points in both groups (2.31±0.51 and 2.33±0.37 for early and late postpartum, respectively, p=0.947). The cholesterol level was 142.75±9.74 mg/dL and 156±12.26 mg/dL, respectively (p=0.133). C-reac- tive protein averaged 60±24 mg/dL and 33±18 mg/dL for early and late postpartum buffaloes, respectively (p=0.137). At the same time, fibrinogen levels were 318.5±161.77 mg/dL for early postpartum and 318.83±69.78 mg/dL, respectively (p = 0.914). C-reactive protein and cholesterol levels were negative- ly correlated (r = -0.71, p=0.048). Because no differences were observed in the variables studied in both postpartum moments, it is possible to suggest that a body condition score lower than 3.0 and persistent levels of C-reactive protein, fibrinogen, and cholesterol could be related to a prolonged period of anestrus in primiparous water buffaloes. However, given the reduced number of animals included and the absence of cyclic females, the results reported should be taken cautiously and verified in a larger population.